1997
DOI: 10.1006/anbe.1996.0461
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetrical turning during spermatophore transfer in the male smooth newt

Abstract: Abstract. During mating, male smooth newts, Triturus vulgaris, showed a population bias for turning left during spermatophore transfer. This is the first demonstration of asymmetrical sexual behaviour in an amphibian population. An experiment with a perfect female model showed that it was due to male rather than female lateralization. Left turning bias decreased progressively as more spermatophores were deposited, and no significant bias was detectable by the third deposition. The hypothesis that this was due … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0

Year Published

1997
1997
2006
2006

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 33 publications
0
19
0
Order By: Relevance
“…For example, recent evidence indicated that the placement of an organism's eyes may contribute to hemispheric and associated behavioral asymmetries (Vallortigara, Rogers, & Bisazza, 1999). Numerous studies found gender differences across species, leading to the argument that hormones can direct asymmetrical development of the nervous system (e.g., Bisazza, Facchin, Pignatti, & Vallortigara, 1998;Green, 1997;Marczinski et al, 1998;Mead & Hampson, 1996). In addition, the postnatal demands of a terrestrial versus aquatic environment may create very different evolutionary pressure.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…For example, recent evidence indicated that the placement of an organism's eyes may contribute to hemispheric and associated behavioral asymmetries (Vallortigara, Rogers, & Bisazza, 1999). Numerous studies found gender differences across species, leading to the argument that hormones can direct asymmetrical development of the nervous system (e.g., Bisazza, Facchin, Pignatti, & Vallortigara, 1998;Green, 1997;Marczinski et al, 1998;Mead & Hampson, 1996). In addition, the postnatal demands of a terrestrial versus aquatic environment may create very different evolutionary pressure.…”
Section: Discussionmentioning
confidence: 97%
“…Motor asymmetries in toads appear to be species and task speci®c (Bisazza, Cantalupo, Robins, Rogers, & Vallortigara, 1997;Robins, Lippolis, Bisazza, Vallortigara, & Rogers, 1998). The limited work on reptiles reveals lateralized courtship behavior in newts (Green, 1997) and lateralized aggressive behavior in lizards .…”
mentioning
confidence: 97%
“…These and other motor lateralities have been demonstrated in many diverse species such as fish (Bisazza, Cantalupo, Capocchiano, & Vallortigara, 2000;Bisazza, Sovrano, & Vallortigara, 2001;Facchin, Bisazza, & Vallortigara, 1999), newts (Green, 1997;Marzona & Giacoma, 2002), toads (Bisazza, Cantalupo, Robins, Rogers, & Vallortigara, 1996, birds (Casey & Martino, 2000;Regolin, Vallortigara, & Zanforlin, 1995), rats (Diaz-Palarea, Gonzalez, & Rodriguez, 1987), primates (Westergaard & Suomi, 1996), and humans (Bracha, Seitz, Otemaa, & Glick, 1987;Bradshaw & Bradshaw, 1988). Previous research has demonstrated that the development of turning biases in bobwhite quail (Casey & Lickliter, 1998) and domestic chicks (Casey & Karpinski, 1999) may be influenced by prenatal visual experience.…”
mentioning
confidence: 94%
“…The behavioural preference of an individual favouring its left or right side when engaging in a task has been documented in mammals, birds, fishes, amphibians, reptiles, and arthropods (Green 1997;Hopkins et al 1997;Bisazza et al 1998;Ades & Ramires 2002;Watkins et al 2003;Rutledge & Hunt 2004). Laterality is thought to be predominantly a result of cerebral functional asymmetry, and is a fundamental feature of both vertebrates and invertebrates (Bisazza et al 1998).…”
Section: Introductionmentioning
confidence: 99%
“…As other functions positioned in the brain's left and right sides interact with movement co-ordination, laterality probably co-evolved with other functions of the brain (Bisazza et al 1998). Thus, behaviours that express laterality are diverse and include: (1) the preference of using one eye over another when searching for predators, competitors or food (Robins et al 1998;Franklin III & Lima 2001;Ventolini et al 2005); (2) the preference of rotating the body one way over another hearing a sound stimulus (Csermely 2004), when escaping predators (Watkins et al 2003;Bisazza et al 2004), and during sexual behaviours (Green 1997;Petersen et al 2001); and (3) tool handling (Rutledge & Hunt 2004).…”
Section: Introductionmentioning
confidence: 99%